Optimalisasi Branding UMKM Mikasi Drink Dengan Pemanfaatan Media Sosial Sebagai Strategi Pemasaran - Eka Satya Nugraha; Sonja Andarini (Yayasan Daarul Huda Kruengmane, 2023)
Current technological developments are of course developing very rapidly with the passage of time, this certainly has an impact on the branding of an UMKM product. With UMKM branding, of course, it can increase sales and also attract consumer interest. UMKM branding can certainly be done in various ways such as creating social media, creating product logos, creating product content and registering UMKM google maps. By doing this, it certainly has a good impact on UMKM and is more easily recognized by the public. Apart from this, SMEs certainly have problems or obstacles in carrying out their product development. One UMKM named Mikasi Drink which is in Pulosari Village, Bareng District, Jombang Regency certainly has several obstacles regarding product development and marketing. Therefore, this journal plans a good strategy for these UMKM so that they can continue to exist and be better known to the public. The method used by researchers is qualitative in nature with the type of data collection through interviews, observation and documentation of UMKM actors. The results of this research certainly make these UMKM experience development in terms of quality and quantity and also help in terms of product marketing either through social media or promotions.